The Role of the Authenticity of Iranian Brands on the Emotional Attachment of Sports Goods Consumers, with Customer Bias as a Mediator - Roghayeh Sarlab; Nahid Darooghe Arefi; Maryam Seidler; Fateme Zare (Sports Business Journal)
Purpose: Domestic sports brands seek to establish consumer relations with the brand to survive and earn continuous profits among foreign competitors. Therefore, this manuscript investigates the effect of domestic brands' authenticity on consumers' emotional dependence on domestic sports goods, including the Daei, Majid, and Momentum brands, with customer bias as a mediator.Methodology: This study was based on a practical purpose and a descriptive correlation data collection method conducted in the field. The statistical population was all consumers of domestic sports goods (Daei, Majid, and Momentum brands), and 191 people were selected as a statistical sample based on the law of structural equations (five times the number of observable variables). The research tools included three Kadirov's (2010) brand authenticity questionnaires, Lee et al.'s (2013) customer bias, and Thomson et al.'s (2005) emotional attachment. Experts confirmed the formal and content validity and the reliability of the questionnaires, estimated to be 0.7, 0.92, and 0.95, respectively. Statistical analysis was performed using SPSS/25 and Smart-PLS.3.2.8 software.Findings: The research results indicated a positive and significant relationship between brand authenticity, emotional attachment, and customer bias. However, there was no significant relationship between customer bias and emotional attachment.Originality: So far, no research has investigated the mediation of customer bias in the relationship between brand authenticity and consumer emotional attachment; therefore, this research is original.